2021
DOI: 10.11591/ijphs.v10i4.20775
|View full text |Cite
|
Sign up to set email alerts
|

Prevention behavior of community for spreading COVID-19 in West Kalimantan Province, Indonesia

Abstract: The COVID-19 pandemic caused huge impacts on human being worldwide. The accumulated infected cases are 156,778,078 with 3,272,054 death cases on May 7, 2021. Importantly, not many people practice the prevention behavior of COVID-19 pandemic. This study measured the prevention behavior of COVID-19 in West Kalimantan Province, Indonesia by socio-demographic factors and protection motivations from the community. This study used a cross-sectional design which was carried out for two weeks from the end of July to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Government employees Int J Public Health Sci ISSN: 2252-8806  Knowledge, motivation, attitude, job design and health cadre performance: … (Rinayati) 387 engage significantly more in volunteering than their counterparts in the private sector. This is also consistent with research that lower knowledge was found among the unemployed individuals and students than working individuals [21].…”
Section: The Characteristics Of Respondentssupporting
confidence: 92%
“…Government employees Int J Public Health Sci ISSN: 2252-8806  Knowledge, motivation, attitude, job design and health cadre performance: … (Rinayati) 387 engage significantly more in volunteering than their counterparts in the private sector. This is also consistent with research that lower knowledge was found among the unemployed individuals and students than working individuals [21].…”
Section: The Characteristics Of Respondentssupporting
confidence: 92%
“…Although in the effort to break the chain of the spread of the COVID-19 pandemic, the government had issued an appeal to reduce social interactions by social and physical distancing [7]. So Indonesian people take various methods of prevention behavior to the transmission of COVID-19 [8]. In several regions in Indonesia, large-scale social restrictions (pembatasan sosial berskala besar/PSBB) and temporary restrictions on the operation of land, sea, and air transportation facilities have ) and solving the problem of spreading COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Pengetahuan tentang Covid-19 signifikan mempengaruhi perilaku pencegahan Covid-19 8,9 . Selain itu, persepsi tentang Covid-19 juga berkontribusi signifikan pada perilaku pencegahan Covid-19 [10][11][12] .…”
Section: Data Dari Gugus Tugasunclassified